GLORIA Survey Of The Gulf Of Mexico - Bonnie A. McGregor (International Marine Minerals Society, 1986)
The U. S. Geological Survey in cooperation with the Institute of Oceanographic Sciences (IOS), U.K., conducted a sidescan sonar survey of the U. S. Exclusive Economic Zone in the Gulf of Mexico from August 7 to October 22, 1985. A reconnaissance-scale view of 120,000 square nautical miles of sea floor seaward of the shelf-edge was obtained by using the GLORIA (Geologic Long-Range Inclined Asdic) sidescan sonar system. After these data were merged with GLORIA data from an earlier survey (1982) of the northwestern Gulf, a preliminary mosaic was constructed at a scale of 1:375,000. From this mosaic, we can identify morphologic features and interpret sea-floor processes. The extensive deformation of the continental slope seaward of Texas and Louisiana by salt tectonics has resulted in a complex pattern of basins and salt dome highs. One continuous meandering channel was identified in this portion of the Gulf, extending from the shelf edge to the Sigsbee Abyssal Plain. Bottom currents have reworked the sediments in this channel's levees seaward of the Sigsbee Escarpment, the seaward edge of the salt front, suggesting that this channel may no longer be actively transporting sediment. Talus appears to lie along the base of the Sigsbee Escarpment, suggesting that erosion and deposition is occur- ring along this front. Three other discontinuous channel systems can be identified on the mosaic and appear to have contributed sediments to the deep Gulf.